Surgical Infection of the Hands and Upper Extremities in Adult Patients Presented to Emergency Departments at Some Khartoum State Teaching Hospitals - Elmahi, Anas Yousif Elgorashi; Hamza, Aamir Abdullahi (Gezira Journal of Health Sciences, 2019)
Background: Hand and upper extremity(HUE) is extremely important in performing day-to-day activities, ranging from simple to very complex tasks. This makes HUE vulnerable to trauma, subsequent infections and a wide spectrum of complications. Objectives: to study the pattern of infection, the anatomical sites distribution, causative organisms, and management offered and the outcome. Patients and methods: This was a prospective, descriptive, cross-sectional, hospital-study. It was a multicentric study, conducted at Khartoum state teaching hospitals, Sudan. During the period from August to October 2019.  All patients with HUEI attending emergency department in Khartoum state hospitals, were enrolled. Non probability sampling including patient consecutively. Questionnaire were used and included the following variables: type of infection, anatomical site, management done, culture and sensitivity of the offending organism and outcome of treatment. Patients’ informed consent and ethical clearance were obtained in advance. Data was analysed using SPSS version 22.0. and the P value was considered significant if < 0.05. Results: this study included 68 patients who satisfied the inclusion criteria. The meanage±SD of patients was 32±14.2 years(ranged from 18 - 68). There is male preponderance 53 (77.9%) with M:F ratio of 3.5:1. Most common causes for HUEI were trauma (47%), puncture or laceration (22%), unknown causes (10%),and postoperative infections (7.4%). Animal bites 2.9%. Spontaneous infections (1.5%), foreign body (1.5%), insect bites (1.5%) other causes (6%). Most frequent site to encounter infection was fingers (20.5%),palm (19.1%), proximal forearm (11.7%), wrist and distal forearm (7.3%),upper arm (3%). Dominant hand affection(69%).Superficial type of infection was found in (60%),and deep in (40%) of the patient. Management included; wound debridement (67.6%), incision and drainage of abscess (29.4%), with antibiotics(97%) of patients. Out of the total patients the admission rates was (56%), Complications rate (85%).Most common isolated organisms in culture were Staph. aureus (52%), Pseudomonas (21%), E.coli (20%), Enterococcus faecalis (11%), Klebsilla (9%), Citrobacter (9%). Other organisms isolated were Staph epidermidis , Streptococcus , Proteus , Acintobacte r.MRSA was found in (38%)of cultures. The commonest complications encountered were; delayed wound healing(31%),cellulitis(19%),joint stiffness(16%),and deformities(12%). Necrotizing fasciitis, sepsis and others developed in (7.5%).The mean length of hospital stay was 9±10.3 day. Conclusion: Complications rate in patients with HUEI is high, a new management guide should be incorporated in the system. MRSA is also an merging problem; infection control departments should take role concerning this.